EFFECTS OF SEAWATER ACCLIMATIZATION ON GILL Na -K -ATPase ACTIVITIES AND CHLORIDE CELLS IN RAINBOW TROUT (On corhynchus mykiss) AND B ROWN TROUT (S almo trutta forma fario) - V. Kızak; O. Ozden; Yusuf Guner (Journal of Animal and Plant Sciences, 2013)
In this study, rainbow trout (Oncorhynchus mykiss) (162.7 ± 3.03 g) and brown trout (Salmo trutta forma fario) (160.9 ± 2.94 g) were transferred to full-strength seawater (36.5 g .l -1) for directly and gradually (21 days), then changes in gill Na+ -K + -ATPase activity and size of chloride cells associated with environmental salinity were investigated and also survival of trouts were evaluated in seawater. All fish died when brown trouts were transferred into seawater directly but rainbow trouts survived 50 – 58.3 %. However, significant difference was recorded between brown and rainbow trouts in terms of survival rates by gradual acclimation. Survival of brown trout and rainbow trout that were transferred in seawater gradually, was 66.7 – 75 % and 83.3 – 91.7 %, respectively (p < 0.05). Gill chloride cell sizes in both species increased at 36.5 g .l -1 salinity. The lowest sectional area of chloride cells was determined at the point of death in brown trouts which were transferred directly. Following direct transfer to seawater, the largest sectional area of chloride cells were determined in rainbow trout. There are significant differences between acclimated and non-acclimated fish in terms of chloride cell sizes and Na+ -K + -ATPase activities (p < 0.05). The highest gill Na+ -K + -ATPase activity was in brown trouts which were transferred gradually, while the lowest activity was detected in freshwater phase. According to the results, gradually acclimated trouts can perform better adaptation than their directly acclimated counterparts.
Keywords: Rainbow trout; brown trout; seawater acclimation; Na -K -ATPase; chloride cell size